GENDER ISSUES IN MULTICULTURAL GUIDANCE AND COUNSELING - Habsy, Bakhrudin All; Nashihah, Durrotun; Hutauruk, Andrea Briliana Christie; Indah, Nur Mutiara (PT Altin Riset Publishing, 2025)
This study aims to deeply analyze gender issues in multicultural guidance and counseling practices in Indonesia and formulate a conceptual model of counseling that is gender-equitable and sensitive to the local cultural context. The research approach used is qualitative with a phenomenological design, with participants consisting of school counselors, guidance and counseling lecturers, and prospective counselor students who were purposively selected. Data were collected through in-depth interviews, observation, and document analysis, then analyzed using thematic analysis techniques. The results showed that counselors' understanding of gender is still normative and influenced by cultural and religious values. Gender bias and stereotypes are still evident in counseling practices, while the counseling strategies applied tend to emphasize social harmony rather than individual empowerment. The main obstacle lies in the lack of training and institutional support for gender-perspective counseling. This study produces a conceptual model that integrates three main dimensions: counselors' awareness, knowledge, and skills in dealing with gender issues in multicultural contexts.